Implementation of Islamic Education and The Religiosity of Moslem Baduy Community in foundation at-Taubah 60 Kampung Landeuh Lebak Banten - Sopian, Achmad (Proceeding International Conference on Religion, Science and Education, 2022)
This study discusses about the Implementation of Islamic and the religiosity of the Moslem Baduy community after religious conversion in foundation at-Taubah 60 Kampung Landeuh Lebak Banten. This research is based on the religiosity problem of the Moslem Baduy in Suku Baduy to reveal the Islamic community of the Baduy, and the implementation of Islamic education carried out by the Baduy after religious conversion. This research is aimed at responding to the following question: (1) The Implementation of Islamic Education at the Moslem Baduy community after religious conversion in foundation at-Taubah 60 Kampung Landeuh Lebak Banten. 2) The religiosity of the Moslem Baduy community after religious conversion in foundation at-Taubah 60 Kampung Landeuh Lebak Banten. This research is a descriptive-analytic study with an ethnographic approach. The data were collected through giving observation, questionnaires, and documentation. The validity test used Triangulasi. The data were analyzed using a descriptive model. The results showed that the implementation of Islamic education carried out by a Moslem Baduy in the form of Islamic studies such as faith, fiqh, morals, etc. Therefore, the implementation of Islamic education of the moslem baduy resulted in the strengthening of the Muslim faith and love of Islam. This study shows that the dynamic religiosity of the Moslem Baduy community after religious conversion in foundation at-Taubah 60 Kampung Landeuh Lebak Banten. This conclusion is derived from the findings the religious conversion of the Moslem Baduy community is driven by internal factors, namely social inequality; those are the lack of understanding of the Baduy people towards the teachings of Sunda Wiwitan and the limitation of land for farming. The external factors are caused by theological, psychological, and sociological factors. Based on the process, the religious conversion of the Moslem Baduy community occurred en masse and individually; both of which were included in the category of active and comprehensive converts.